2008
DOI: 10.1007/s11010-008-9766-9
|View full text |Cite
|
Sign up to set email alerts
|

Rafts making and rafts braking: how plant flavonoids may control membrane heterogeneity

Abstract: Plant flavonoids are not only known as powerful antioxidants, but also as cell metabolism regulators. It has been postulated that they are able to control cell signal pathways by targeting receptors on the cell surface or by intercalating the lipid bilayer of membranes. Some flavonoids can increase lipid viscosity and decrease the cooperativity of hydrocarbon chain melting, while others can considerably decrease the lipid melting temperature, thus providing additional freedom for lipid diffusion. Here we discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
3
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 61 publications
4
66
3
7
Order By: Relevance
“…It was showed that the T 50 mins were longer than 3 and a half hours. Plant polyphenols are membrane-active antioxidant agents (Saija et al, 1995) and are the cell metabolism regulators by modulating the fluidity of lipid bilayer, since they have been demonstrated to control cell signal pathways by targeting receptors on the cell surface or by intercalating the lipid bilayer of membranes (Tarahovsky et al, 2008). Polyphenols interact with the surface of bilayer through hydrogen bonding have been shown to reduce the accessibility of oxidants, thus protecting the structure and function of membranes (Oteiza et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…It was showed that the T 50 mins were longer than 3 and a half hours. Plant polyphenols are membrane-active antioxidant agents (Saija et al, 1995) and are the cell metabolism regulators by modulating the fluidity of lipid bilayer, since they have been demonstrated to control cell signal pathways by targeting receptors on the cell surface or by intercalating the lipid bilayer of membranes (Tarahovsky et al, 2008). Polyphenols interact with the surface of bilayer through hydrogen bonding have been shown to reduce the accessibility of oxidants, thus protecting the structure and function of membranes (Oteiza et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the lipid organization indicate changes in the physicochemical properties of the cell lipid bilayer membrane by, e.g., reduction in hydrophobicity of the lipid membrane interior, change in organization and fluidity of the bilayer and disorders of the lipid asymmetry and depolarization of the membrane [19][20][21]. As a consequence of those changes, an inhibition of the activity of the enzyme and transport of proteins and loss of membrane integrity may occur, leading to cell's death.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that RBCs were resistant to AAPH-induced oxidation when ARE in the 100 -600 mg/L concentration range were supplemented. Flavonoids may regulate cell metabolism by modulating the bilayer state since they have been demonstrated to control cell signal pathways by targeting receptors on the cell surface or by intercalating the lipid bilayer of membranes (Tarahovsky et al, 2008). In addition, interactions of flavonoids at the surface of bilayer through hydrogen bonding have been shown to be crucial in reducing the accessibility of oxidants, thus protecting the structure and function of membranes (Oteiza et al, 2005).…”
Section: Discussionmentioning
confidence: 99%